PENGARUH PEMBELAJARAN DARING TERHADAP INDEKS PRESTASI KUMULATIF MAHASISWA FKIP UNTAN. - Sutriani, Dwi; Asriati, Nuraini; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Online learning is learning that is carried out online, using learning applications and others social network. Whit online learning it is expected to be able to achieve better student Grade Point Average (GPA) result. The objectives of this study are: (1) To find out how online learning is carried out for Economics Education students at FKIP UNTAN. (2) To find out the GPA of Economics Education students in implementing online learning at FKIP Untan. (3) To find the effect of online learning on the Grade Point Average (GPA) of FKIP Untan students. In this study, researcher used a quantitative approach to the survey method. The technique used is indirect communication. The data collections tool used is a questionnaire. The result of the study show that there is no influence between online learning and the Grade Point Average (GPA), which can be seen from the result of a simple linear regression, namely trhough the t test, the magnitude is 0.05. Known it is that t count is -0.981 and a significance of 0.332. Meanwhile the result obtained for t table were 2.014. Thus, it is known that the value of t count t table (-0.9812.014), and a significance of 0.05 0.0332 then Ha is rejected.